Part A.) the answer is B:9
Part B.) together their total score is -3
Question:
Expand and simplify 5(x - 1) - 3(x + 4)
Answer:
1.) Use the distributive property to solve this equation:
5(x - 1) = 5x - 5
3(x + 4) = 3x + 12
2.) Put it in the equation:
5x - 5 - 3x + 12
3.) Group them:
5x - 3x - 5 + 12
4.) Simplify:
2x - 7
which is the answer.
Hope this helped! :))
Answer:
1421/576
Step-by-step explanation:
Sum = - 13/8 + 5/12 = - 39/24 + 10/24 = - 29/24
Difference = - 13/8 - 5/12 = - 39/24 - 10/24 = - 49/24
Sum * Difference = (-29/24)*(-49/24) = 1421/576